(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study aims to analyze how the Graciliano Ramos State Public Library is structured to welcome and integrate librarians with Autism Spectrum Disorder (ASD) into its institutional environment. Methodologically, this is a descriptive study that employed field research and systematic observation from a qualitative analysis perspective. The results indicate that the Graciliano Ramos State Public Library has made significant progress in terms of accessibility, sensory aspects, and physical-structural space. The presence of elements that promote inclusion was observed, although minor improvements are still needed to ensure a more welcoming, functional, and adaptable environment for the diverse needs of users and staff. The Graciliano Ramos State Public Library is considered to have the potential to welcome future staff members with Autism Spectrum Disorder, provided that adjustments are made to the institutional environment to promote inclusion, well-being, and the full integration of these professionals.